Higher Education Aid Policy Public and Private - Firdausi, Lutfi (Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze the policy of providing higher education assistance in public and private educational institutions. Higher education has an important role in the development of human resources and the development of a country. Higher education assistance is one of the policy instruments used by the government to improve the accessibility and quality of higher education. The research method used in this study is policy analysis. The data used comes from various sources, including policy documents, research reports, and statistical data related to the provision of higher education assistance in public and private educational institutions. The analysis was conducted by comparing the policies of higher education assistance in both types of educational institutions. The results of this study are expected to provide a better understanding of the policy of providing higher education assistance in public and private educational institutions. The analysis will involve aspects such as the criteria for receiving aid, the amount of aid provided, the requirements to be met by recipients, and the impact of policies on accessibility and quality of higher education